The “naturalism” of Descartes and the naturalism of “Cartesians” - Drozdowicz, Zbigniew (Humaniora. Czasopismo Internetowe, 2019)
My deliberations seek to demonstrate that Descartes’s philosophy is programmatically anti-naturalistic, while its being presented and interpreted as one of the possible forms of naturalism evinces misunderstanding of its basic principles. For this reason, Descartes’s “naturalism” is referred to using quotation marks. Admittedly, his philosophy does advance such postulations and assertions which lend themselves to interpretation in naturalistic categories, but only when they are abstracted from the broader entirety of the Cartesian philosophical system. The text provides only two such examples, though more could be found in the seventeenth-century though. In each case, they constituted a departure from the very foundations of that system.